Faktor-Faktor yang Mempengaruhi Penggunaan Narkoba pada Remaja di Pemukiman Kumuh Desa Perbarakan Pagar Merbau Tahun 2024 - Tiara Amanda Br. Sembiring; Heppy Jelita Sari Batu Bara (Lembaga Pengembangan Kinerja Dosen, 2026)
Drug abuse among adolescents living in slum areas has become a serious problem requiring special attention. This study aims to analyze the factors influencing drug use among adolescents in slum areas in Perbarakan Village, Pagar Merbau. Using a cross-sectional design, this study involved 16 adolescent drug users selected through total sampling technique. Data were collected using closed questionnaires and analyzed using chi-square test. The results showed significant relationships between slum conditions (p=0.032), education level (p=0.006), economic status (p=0.032), and peer influence (p=0.006) with drug abuse. The majority of respondents (75%) lived in severe slum conditions, 87.5% had secondary education or lower, 75% came from low economic class, and 81.3% associated with drug users. This study concludes that drug abuse prevention and treatment interventions need to comprehensively consider environmental, social, economic, and educational factors.